2019
DOI: 10.1111/1751-7915.13371
|View full text |Cite
|
Sign up to set email alerts
|

In silico prospection of microorganisms to produce polyhydroxyalkanoate from whey: Caulobacter segnis DSM 29236 as a suitable industrial strain

Abstract: Summary Polyhydroxyalkanoates ( PHA s) are polyesters of microbial origin that can be synthesized by prokaryotes from noble sugars or lipids and from complex renewable substrates. They are an attractive alternative to conventional plastics because they are biodegradable and can be produced from renewable resources, such as the surplus of whey from dairy companies. After an in silico screening to search for ß‐galactosidase and PHA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 91 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…The creation of a categorized genomic list of potential PHA producing microbes presents a valuable resource that directs researchers to explicit candidates, as well as access to potential metabolic pathways of interest. A similar bioprospecting strategy was utilized successfully by Bustamante et al (2019) using in silico screening methods to screen for putative PHA and β-galactosidase genes in a select number of microorganisms from literature to find PHA producers that could hydrolyze lactose for utilizing excess whey produced from the dairy industry as a cheap feedstock alternative. In comparison, our study has presented a broader scope by using genomes from large-scale data repositories in the public domain, allowing researchers access to a wider array of candidates which can be sorted by PhaC class, taxonomy and ecological information.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of a categorized genomic list of potential PHA producing microbes presents a valuable resource that directs researchers to explicit candidates, as well as access to potential metabolic pathways of interest. A similar bioprospecting strategy was utilized successfully by Bustamante et al (2019) using in silico screening methods to screen for putative PHA and β-galactosidase genes in a select number of microorganisms from literature to find PHA producers that could hydrolyze lactose for utilizing excess whey produced from the dairy industry as a cheap feedstock alternative. In comparison, our study has presented a broader scope by using genomes from large-scale data repositories in the public domain, allowing researchers access to a wider array of candidates which can be sorted by PhaC class, taxonomy and ecological information.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify new efficient PHA producers from whey, in silico prospection has proven to constitute a successful strategy. For instance, Caulobacter segnis DSM 29236 accumulates 37% of cell dry weight (CDW) in PHB, producing 9.3 g L −1 in fed-batch cultures [97]. Conversely, the lactose monomers, glucose and galactose, are commonly mineralized by many bacteria; consequently, a hydrolytic pretreatment could broaden the range of bacteria capable of fermenting such a waste stream.…”
Section: Bacterial Biopolymer Production From Renewable Sourcesmentioning
confidence: 99%
“…Therefore, there is a need to look for microorganisms that accumulate high levels of these biopolyesters using whole cheese whey as a carbon source. Bustamante et al [ 49 ] revealed that Caulobacter segnis DSM 29236 in the fed-batch fermentation reached up to 9.25 g L −1 of P(3HB) by directly hydrolyzing lactose from whey. So far, it is the highest reported P(3HB) concentration in the growth of pure bacterial culture using whole cheese whey without any pre-treatments processes.…”
Section: Phas Biosynthesis Using By-products Of the Dairy Industrymentioning
confidence: 99%